Sosialisasi Efek Negatif Perkembangan Teknologi pada Remaja di SMK YPK Imanuel Kota Sorong - Faroek, Dewi Astria; Tella, Fitriyani; Ermin; Yusuf, Muhammad; Nurdjan, Nirwana; Nurfitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Technology is the result of human thought, which develops certain procedures and uses them to solve problems in human life. Indonesian people tend to prefer online activities over offline ones. Technology presents many dangers and threats, such as theft of personal data. The negative impact of technology can also give teenagers game addiction, gambling done via the internet, and decreased interest in learning. On the other hand, technology also has positive impacts, such as making it easy to find the information you need and being able to access anything easily. So, it is necessary to carry out outreach for teenagers at YPK Immanuel Vocational School in Sorong City. Participants will be given socialization by providing materials and a question and answer session. The socialization participants were students of classes X and XI at SMK YPK Imanuel, Sorong City. The number of participants who took part in the socialization was around 75 students. This activity is very important to provide insight and views to participants who are wise in using technology and can understand the impact of the negative effects of developing technology.